Knowledge of the National Health Act among Physicians in two Tertiary Hospitals in Southern Nigeria - Oluseyi Adejumo; Cynthia Roli; Oludamilola Adebola Adejumo; Oladimeji Adedeji Junaid; Sunday Samson Owolade (Babcock University Medical Journal, 2022)
Objective: Knowledge of provisions of the National Health Act among physicians and stakeholders is pivotal to its successful implementation. This study aimed to assess the knowledge of the National Health Act (NHA) among Physicians in two tertiary hospitals in Nigeria.